PEMBENTUKAN KARAKTER KERJASAMA DAN CINTA TANAH AIR MELALUI PEMBELAJARAN TEMATIK MODEL WEBBING DI SEKOLAH DASAR PONTIANAK TIMUR - Ngatini, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aimed to describe the thematic learning model of webbing for the formation of the character of cooperation and patriotism in third class State Elementary School 12 East Pontianak. This research is a descriptive qualitative approach. Subjects in this study were teachers and students of third classÂ State Elementary School 12 East Pontianak. The data collection is done by observation, interview and documentation. Data analysis is done through the following phases: data reduction, data display, and conclusion. Mechanical examination of the validity of data by using triangulation. The results of this study indicate that the thematic learning model of webbing in its implementation found some positive action that has inspired teachers and instill character and patriotism cooperation through habituation learners through fun learning activities and be done continuously. Establishment of cooperation attitude and love of the homeland to the elementary school students can apply through thematic learning model of webbing.Â Key words :Â thematic learning, webbing model, cooperation, patriotism